Autophagy characteristics of phytoestrogens in management and prevention of diseases: A narrative review of in-vivo and in-vitro studies - Khater, Safaa I; Shalabi, Maram; Alammash, Buthainah B; Alrais, Alaa I; Al ahmadi, Doaa; Alqahtani, Leena S; Khamis, Tarek; Abdelaziz, Sahar; Aldawy, Khalifa (Journal of Advanced Veterinary and Animal Research, 2023)
Phytoestrogens are non-steroid polyphenolic materials present in 300 plants. Regarding their structural similarities to estradiol, phytoestrogens attach to estrogen receptors and display anti or pro-estrogenic activities. This review explored phytoestrogens’ potential advantages and autophagy properties in light of their future application for disease management, highlighting how phytoestrogens could modulate autophagy. Research has examined the prospective benefits of phytoestrogens for the anticipation and management of various conditions, including signs of menopause, tumors, skin deterioration, osteoporosis, heart disease, neurodegenerative conditions, disorders of the immune system, and metabolic syndrome, owing to their therapeutic effects. As phytoestrogens can activate or inhibit autophagy, which has antioxidant, apoptotic, anti-mutagenic, anticancer, transcriptional, and genomic impacts on cancer and aging illnesses, phytoestrogens could influence diseases through the modulation of autophagy. The collaborative research on animal models, utilization of genetic techniques, and administration of pharmacologically active substances has indicated the possible therapeutic benefits of autophagy modulation in various illnesses. Further research is required to illustrate the pathways by which phytoestrogens modulate autophagy and the possible therapeutic effects on these diseases. J. Adv. Vet. Anim. Res., 10(2): 308–320, June 2023 http://doi.org/10.5455/javar.2023.j683